DNA damage‐inducible transcript 3 immunohistochemistry is highly sensitive for the diagnosis of myxoid liposarcoma but care is required in interpreting the significance of focal expression. Issue 1 (14th April 2021) - Vargas, Ana Cristina; Chan, Noni L; Wong, Daniel D; Zaborowski, Matthew; Fuchs, Talia L; Ahadi, Mahsa; Clarkson, Adele; Sioson, Loretta; Sheen, Amy; Maclean, Fiona; Bonar, Fiona; Cheah, Alison; et al.
Abstract : Aims: Myxoid liposarcoma (MLPS) is characterised by DNA damage‐inducible transcript 3 (DDIT3) gene rearrangements, confirmation of which is commonly used diagnostically. Recently, DDIT3 immunohistochemistry (IHC) has been reported to be highly sensitive and, when strict criteria are employed, specific for the diagnosis of MLPS. The aim of this study was to independently investigate DDIT3 IHC as a diagnostic marker for MLPS. Methods and results: DDIT3 IHC was performed on 52 MLPS and on 152 mimics on whole sections, and on 515 non‐MLPS sarcomas in tissue microarray format. Only one MLPS (which had undergone acid‐based decalcification) was completely negative. With inclusion of this case if any nuclear expression is considered to indicate positivity, the overall sensitivity of DDIT3 is 98% (51 of 52 cases) and the specificity is 94% (633 of 667 non‐MLPS cases are negative). If a cut‐off of >10% of neoplastic cells is required for positivity, then the sensitivity remains 98% (51/52) and the specificity is 98.5% (657 of 667 non‐MLPS cases are negative). If a cut‐off of >50% of cells is required for positivity, then the sensitivity is 96% (50 of 52 cases) but the specificity improves to 100%. Conclusions: Diffuse nuclear DDIT3 expression occurs in the overwhelming majority of MLPSs, and can be used to confirm the diagnosis in most cases without the need for molecular testing. A complete absence of expression argues strongly against MLPS, and almost completely excludes this diagnosis, particularly if there is consideration of technical factors such as decalcification. The significance of focal DDIT3 expression should be interpreted in the morphological and clinical context, although most tumours showing only focal expression are not MLPS. Abstract :